Pastoral resilience: Navigating complexity and managing risks in drylands - Jameel Observatory for Food Security Early Action (University of Edinburgh, 2024)
Covering two-thirds of Africa, drylands are home to half a billion people. These landscapes are vital for the livelihoods and ecological diversity they support. Pastoralism, a way of life evolved over centuries, is fundamental to the livelihoods of millions, offering food security and contributing to national economies. Yet, drylands face severe challenges: climatic fluctuations, resource scarcity, and socio-political pressures that threaten traditional ways of life. Misunderstandings about drylands and pastoralism lead to policies that marginalize these communities, limiting their growth and resilience. Addressing these issues demands early action and investment focused on robust evidence, responsive policies, and community empowerment.